Manajemen dan Terapi Acute Respiratory Distress Syndrome pada Pasien yang Terinfeksi Virus Covid-19 : Sebuah Review - Aldo Josua Valentino Sinaga; Flora Rumiati; William William (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
COVID-19 is able cause Acute Respiratory Distress Syndrome (ARDS) which is animportant factor in the the disease’s severity. This review aims to determine the effect of COVID-19 virus infection on the onset of Acute Respiratory Distress Syndrome (ARDS) and its management therapy. The research used is a literature review, the articles used are obtained through PubMed and Google Scholar and then filtered according to the criteria needed. COVID-19 infection is associated with an inflammatory cytokine storm that can result in acute lung injury. Cytokine storm is an abnormal response of systemic inflammation which occurs due to excessive production of proinflammatory cytokines and chemokines. Respiratory failure such as acute hypoxemia can occur due to manifestations of Acute Respiratory Distress Syndrome (ARDS) and Acute Lung Injury (ALI), not due to increased pulmonary capillary pressure. Management and therapy in lung injury patients such as supportive therapy, administration of antibiotics, and the use of mechanical ventilators are needed to treat the disease.